Household Welfare Effects Of Adopting Open Data Sources for Climate Smart Practices - Akundabweni, Juniour Shadeya; Laura, Barasa; Richard, Mulwa Mbithi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2025)
Despite persistent attempts to address climate change using open data sources, acceptance rates remain low as benefits are not well understood. This study therefore explores the welfare effects of adopting climate smart agriculture practices on smallholder households using data from 436 households collected using a multistage sampling. The impact was estimated using Endogenous Switching Regression . The estimates also provide evidence that the control group , the non adopter had they adopted could have potential increased their welfare by 224547.3. The analysis shows that participation in use of open data for climate smart agriculture would significantly improve households’ annual income by Kshs. 231,5385.The policy implication is that, households can improve their welfare by adopting open data channels for climate-smart practices. The policy implication is that, households can improve their welfare by adopting open data channels for climate-smart practices